The prolonged impact of COVID-19 on symptoms, health-related quality of life, fatigue and mental well-being: a cross-sectional study - Brus, Iris M.; Spronk, Inge; Haagsma, Juanita A.; de Groot, Annemieke; Tieleman, Peter; Biere-Rafi, Sara; Polinder, Suzanne (Frontiers in Epidemiology, 2023)
Background A subset of patients experience persisting symptoms after an acute COVID-19 infection, referred to as “post COVID-19 condition”. This cross-sectional study aimed to compare symptoms, health-related quality of life (HRQoL), fatigue, mental well-being, and determinants of diminished HRQoL, between patients with post COVID-19 condition categorized by time since acute infection. Methods We performed an online survey and analyzed responses of 10,194 adult respondents with a confirmed or suspected COVID-19 infection, who experienced persisting symptoms ≥3 months after the initial infection. The most debilitating symptoms and health outcomes were studied separately for respondents 3–6, 7–9, 10–12, 13–18, 19–24, and >24 months after acute infection. Results At each time period, fatigue, sensory-processing problems, and concentration problems were the most debilitating symptoms reported by respondents, although the proportion of respondents who reported these symptoms differed significantly between time periods. Respondents 3–6 months post-acute infection had the lowest HRQoL (median EQ-5D utility score: 0.59), the highest fatigue level (median score: 110.0) and the highest proportion with a likely depressive disorder (32.4%), whereas respondents 13–18 months post-infection had the highest HRQoL (0.65), the lowest fatigue level (106.0), and the second lowest proportion with a likely depressive disorder (25.0%) (p = 0.000–0.007). Compared to those 13–18 and 19–24 months post-infection, respondents >24 months post-infection had a slightly lower HRQoL (0.60), lower fatigue level (108.0), and lower proportion with a likely depressive disorder (29.2%), although only the differences in HRQoL were statistically significant (p = 0.001–0.010). Younger age, female gender, lower level of education, not having paid work before COVID-19, comorbidity, and not being vaccinated, seemed to be associated with lower HRQoL. Conclusion Regardless of time since infection, respondents considered fatigue, sensory processing problems and concentration problems the most debilitating symptoms. They experienced a low HRQoL and severe fatigue, even more than two years after acute COVID-19 infection. Respondents 3–6 months post-infection had the worst health outcomes, whereas respondents 13–18 months post-infection had the best outcomes, indicating that, at least for a subgroup of patients, health status may improve over time.